Sustainable manufacturing for the future – second white paper - Jolly, Mark R. (Cranfield University, 2016)
This second white paper presents the results of 3 x 3 Month studies on the Pathways for Sustainable Manufacturing tin the future in the Food and Drinks Industry in Great Briatin
Keywords: 'Sustainable Manufacturing'; 'Manufacturing the Future; 2050'; 'Food and Drink Industry Great Britain'; 'Coca-Cola White Paper'; 'Pathways for the future'